Harvesting electrical energy from automatic sliding doors use - Khalit, Muhammad Ilham; Hurtis, Roger Ashley; Khidhir, Basim A.; Anuar, Hazleen (Trans Tech Publications Ltd, Switzerland, 2022)
This paper reflects the energy that can be harvested from the automatic sliding doors. Previously, swinging doors and revolving doors were used to harvest the energy. But due to difficulties to attain a maximum range of motion through the swinging doors which is can open up to 90 0 and because revolving doors take up a lot of spaces and it is not ideal to be located in a small building, thus the use of automatic sliding doors was suggested for this research. This research aims to analyze the output produced from the new system and compare it with the existing systems that use swinging and revolving doors. The kinetic energy attained from the motion of sliding doors then was converted to ambient energy which can be later converted to electrical energy. The system used Piezoelectric generators to generate energy from the motion of sliding doors. There are 3 systems with different wheel diameters and several piezoelectric modules placed within the tires of the wheel. The energy was produced by the deformation in the body of the tires caused by the load applied to the wheels. ANSYS’s software was used to simulate the stress acting on the wheel. It was found out the door produces 60.41 J and 80.52 W of energy and power assuming that the door is used for 120 minutes every day. It was concluded that the energy lost from the motion of sliding doors can be harvested and the system doesn’t take up much space as compared to the revolving doors’ system.